Allied Air Attacks and Civilian Harm in Italy, 1940-1945 Bombing among Friends - Evangelista, Matthew (Routledge Studies in Second World War History, 2023)
Tens of thousands of Italian civilians perished in the Allied bombing raids of World War II. More of them died after the Armistice of September 1943 than before, when the air attacks were intended to induce Italy's surrender.　 Allied Air Attacks and Civilian Harm in Italy, 1940-1945 addresses this seeming paradox, by examining the views of Allied political and military leaders, Allied air crews, and Italians on the ground. It tells the stories of a little-known diplomat (Myron Charles Taylor), military strategist (Solly Zuckerman), resistance fighter (Aldo Quaranta), and peace activist (Vera Brittain) - architects and opponents of the bombing strategies. It describes the fate of ordinary civilians, drawing on a wealth of local and digital archival sources, memoir accounts, novels, and films, including Joseph Heller's Catch-22 and John Huston's The Battle of San Pietro. The book will be of interest to readers concerned about the ethical, legal, and human dimensions of bombing and its effects on civilians, to students of military strategy and Italian history, and to World War II buffs. They will benefit from a people-focused history that draws on a range of eclectic and rarely used sources in English and Italian.